A Mobile Application for Patients With Heart Failure: Theory- and Evidence-Based Design and Testing. Issue 11 (November 2018) - Foster, Marva
Abstract : Self-care is vital for the successful management of heart failure. Mobile health can enable patients with heart failure to perform effective self-care. This article describes the theory-guided development and beta testing of a mobile application intervention to support self-care and increase symptom awareness in community-dwelling patients with heart failure. Ten participants entered physiologic data, answered qualitative questions about symptoms, and reviewed heart failure education within the HF App daily. Two validated instruments, the Self-care of Heart Failure Index and Heart Failure Somatic Awareness Scale, were administered both before and after the intervention, and results were compared using t tests. Results indicated that there were clinically significant changes from preintervention to postintervention in self-care scores in each subscale, with a statistically significant difference in the confidence subscale scores ( P = .037). However, there were no statistically significant differences between preintervention and postintervention symptom awareness scores. These results indicate that incorporating mobile applications that comprise symptom monitoring, reminders, education, and the ability to track trends in physiologic data is most useful to assist individuals with heart failure to perform effective self-care.